2019
DOI: 10.31223/osf.io/5tg68
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coherent streamflow variability in Monsoon Asia over the past eight centuries---links to oceanic drivers

Hung Nguyen,
Sean Turner,
Brendan Buckley
et al.

Abstract: Climate-informed dynamic streamflow reconstruction is skillful over most of Monsoon Asia • Spatial coherence of streamflow suggests water management be coordinated among basins • Mekong and Chao Phraya are most sensitive among rivers to anomalies in sea surface temperature AbstractThe Monsoon Asia region is home to ten of the world's biggest rivers, supporting the lives of 1.7 billion people who rely on streamflow for water, energy, and food. Yet, a synoptic understanding of multi-centennial streamflow variabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…Yet, conclusions drawn on the grid's exposure and response to hydroclimatic variability should be taken with caution, owing to the nonstationarity in the ENSO‐monsoon teleconnection. Analyses conducted over the past centuries—combining observed and paleo‐reconstructed data—revealed that the strength of the teleconnection varied over space and time, alternating decades of weaker and stronger effects (Nguyen et al., 2020; Räsänen et al., 2016). An explanation for this behavior may be sought in the amplitude, temporal evolution, and spatial patterns of ENSO events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, conclusions drawn on the grid's exposure and response to hydroclimatic variability should be taken with caution, owing to the nonstationarity in the ENSO‐monsoon teleconnection. Analyses conducted over the past centuries—combining observed and paleo‐reconstructed data—revealed that the strength of the teleconnection varied over space and time, alternating decades of weaker and stronger effects (Nguyen et al., 2020; Räsänen et al., 2016). An explanation for this behavior may be sought in the amplitude, temporal evolution, and spatial patterns of ENSO events.…”
Section: Discussionmentioning
confidence: 99%
“…Warm conditions in the tropical Pacific (El Niño) delay the monsoon onset and shorten the overall rain season, while cold conditions (La Niña) are associated to wetter conditions in mainland Southeast Asia (Cook & Buckley, 2009; Singhrattna et al., 2005). Third, streamflow in the Mekong and Chao Phraya river basins is spatially coherent, owing to common meteorological and climatological drivers (Nguyen et al., 2020). We thus expect water availability and dispatchable hydropower to show seasonal and interannual modes of variability in both basins.…”
Section: Methodsmentioning
confidence: 99%
“…The results of these reconstructions portend a potential increase in flood events in the future, depending on how these large-scale climate phenomena are affected by climate change (Cai, Sullivan, & Cowan, 2009;Perry, Mcgregor, Gupta, & England, 2017;Zhang & Delworth, 2016). Further, the streamflow reconstructions provide an extended flow dataset ranging from 247 to 800 years in length to test and improve FFA methods (D'Arrigo et al, 2011;Nguyen et al, 2020;Nguyen & Galelli, 2018).…”
Section: Estimating Flood Magnitude and Frequencymentioning
confidence: 99%
“…The phases of ENSO, the Indian Ocean Dipole (IOD), and the Pacific Decadal Oscillation (PDO) all influence the strength and occurrence of the monsoons and tropical storms in SE Asia. In a recent analysis, the reconstruction of 800 years of streamflow in several rivers by Nguyen, Turner, Buckley, and Galelli (2020) was useful in showing that streamflow in Monsoon Asia is spatially coherent, with concurrent high/low flow episodes in adjacent basins because ENSO, IOD, PDO, and tropical Atlantic sea‐surface temperatures are common drivers. Collectively, the effect of these phenomena, often in tandem, vary in location, magnitude and timing, such that extremes are not likely captured in short flow records.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation